Innovation of Business Models and Financial Feasibility of Etawa Goat Cultivation Integrated with Organic Farming - Jahrizal, Jahrizal; Dalil, M.; Junaedi, Achmad Tavip; Tendra, Gusrio; Renaldo, Nicholas (Universitas Pendidikan Ganesha, 2025)
Goat farming holds significant potential as a sustainable livestock business, yet traditional methods often face challenges related to scalability and long-term sustainability. Many conventional farming practices rely heavily on key individuals without structured business strategies, making them vulnerable to discontinuity. To address these issues, a modern and structured business model is necessary. This study aims to explore development strategies for implementing integrated organic farming in Etawa goat cultivation. Using a qualitative approach, this research employs the Business Model Canvas (BMC) framework and financial feasibility analysis to evaluate the viability of the business. The findings reveal that Etawa goat farming can be successfully established and expanded through a well-defined BMC approach, which ensures business sustainability and competitiveness. Furthermore, financial feasibility analysis supports the economic viability of the venture, indicating its potential for long-term profitability. By integrating these strategic tools, Etawa goat farming can achieve sustainable growth, enhancing both productivity and market resilience.